Metoprolol‐Induced Pemphigus‐Like Reaction. Issue 1 (28th September 2018) - Patel, Seena; Kim, Shanna; Allen, Carl
Abstract : Introduction: Pemphigus vulgaris (PV) is a relatively rare, potentially life‐threatening autoimmune disease that, in most cases, has an unknown etiology. Medications for hypertension have been linked to the onset and exacerbation of PV‐like symptoms. The diagnosis of medication‐related PV can be challenging because it has an identical appearance to the clinical and histologic appearance of idiopathic PV and cases may not resolve after discontinuation of the drug. Case Presentation: We present a case of an elderly patient with gingival and cutaneous erosions, who underwent several medical and dental consultations without an appropriate diagnosis. After biopsy and a thorough review of her medical history, metoprolol was suspected as the offending agent. After consulting with her cardiologist, metoprolol was discontinued, and a complete resolution of all lesions resulted. Conclusions: To our knowledge, the current case is the first reported case of metoprolol‐induced PV in the English‐language literature. As such, it highlights the potential of medication involvement in some immune‐mediated diseases. Because the oral mucosa is often the first site of involvement in PV, knowledge of drug‐related PV is crucial in the diagnosis, treatment, and management of dental patients.